Child Sexual Abuse in the United States: Perspectives on Assessment and Intervention - Foster, Jennifer M.; Carson, David K. (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> Child sexual abuse (CSA) is a widespread problem the United States as it is in many areas of the world today. CSA can lead to a host of psychological and emotional difficulties and disorders that can cripple some children and youth for a lifetime. In this article the authors discuss the sexual abuse of minors in the United States. Risk factors involved in and potential causes of CSA are discussed. Signs and symptoms of CSA are summarized along with common consequences associated with sexual abuse. Characteristics of sexual perpetrators of children and adolescents are also examined. In addition, the authors discuss the problems children often have in disclosing the abuse, along with the individual, familial and societal challenges involved in reporting incidences of sexual abuse. Some assessment issues and tools associated with CSA are highlighted, and the importance of investigators and clinicians capturing children's narrative descriptions of their abuse, and various methods for doing so, are outlined. Finally, an overview of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) for children is presented, and common challenges for therapists in treating children who have experienced sexual abuse and their families are discussed. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->